The Correlation of the Family Support with An Anxiety Level of Coronary Heart Disease on Patients - Siti Santy Sianipar; Suryagustina Suryagustina; Evie Eko Indriyani (Universitas Sari Mulia, 2021)
ABSTRACTÂ â€œThe Correlation of the Family Support with An Anxiety Â Levelof Coronary Heart Disease on Patientsâ€Â Siti Santy Sianipar1 Â Suryagustina2 Â Evie Eko Indriyani3Â Â Â Background: Coronary Heart Disease was the high cause of death and is also a commonly curable and often sudden death. Lack of family support can increase patient anxiety and thus affect the healing process. For that, support from the family in patients Coronary Heart Disease in an important factor in reducing anxiety levels. This study was mean to know a correlation of the family support with an anxiety level of Coronary Heart Disease on patients Â Methods:Of this study was a correlational with the statistic test of Spearman Rank. Taking this sample used purposive sampling as much total of 30 respondentsÂ Result: Of this study was an anxiety level, the p value of 0.000 â‰¤ the value ofÂ a = 0.05, so that Ha 1 was accepted where there was a correlation of the family support with an anxiety level.Conclution: There was a correlation between the family support with an anxiety level. The suggestion raised was to give the health educaton to the patientâ€™s family of the Coronary Heart Disease about the importance of family support in reducing an anxiety level in the treatment process.Â Keyword: Coronary Heart Disease, An Anxiety Level, The Family SupportBibliography: 23 (2011-2019)Â Â